Revolutionizing thermoplastic starch: advances in nanocellulose reinforced biocomposites: a review - Mahardika, Melbi; Sudarjat, Khalissa Sekar Amanda; Ilyas, R. A.; Mohamad Kassim, Mohamad Haafiz (Elsevier, 2025)
Plastic-based food packaging has raised significant environmental concerns due to the accumulation of non-biodegradable waste. Starch-based biodegradable films offer a sustainable alternative due to their abundance, biodegradability, and modifiability; however, their practical applications are limited by their low mechanical strength and water resistance. Incorporating nanocellulose, derived from lignocellulosic fibers, into starch matrices effectively overcomes these limitations. Nanocellulose provides high crystallinity, exceptional mechanical strength, and a unique fibrillar morphology, enhancing the structural, barrier, and thermal properties of starch-based films. This review presents a comprehensive overview of starch–nanocellulose biocomposites, including preparation methods, structural and functional characteristics, and potential applications in food packaging, biomedical devices, environmental remediation, and other emerging areas. It also identifies current research gaps, demonstrates how nanocellulose reinforcement improves performance relative to conventional plastics, and highlights future directions for developing sustainable, high-performance, and eco-friendly biocomposites.